Novel insights into carbohydrate utilisation, antimicrobial resistance, and sporulation potential in Roseburia intestinalis isolates across diverse geographical locations - Indrani Mukhopadhya; Jennifer C. Martin; Sophie Shaw; Martin Gutierrez-Torrejon; Nikoleta Boteva; Aileen J. McKinley; Silvia W. Gratz; Karen P. Scott (Gut Microbes)
Roseburia intestinalis is one of the most abundant and important butyrate-producing human gut anaerobic bacteria that plays an important role in maintaining health and is a potential next-generation probiotic. We investigated the pangenome of 16 distinct strains, isolated over several decades, identifying local and time-specific adaptations. More than 50% of the genes in each individual strain were assigned to the core genome, and 77% of the cloud genes were unique to individual strains, revealing the high level of genome conservation. Co-carriage of the same enzymes involved in carbohydrate binding and degradation in all strains highlighted major pathways in carbohydrate utilization and reveal the importance of xylan, starch and mannose as key growth substrates. A single strain had adapted to use rhamnose as a sole growth substrate, the first time this has been reported. The ubiquitous presence of motility and sporulation gene clusters demonstrates the importance of these phenotypes for gut survival and acquisition of this bacterium. More than half the strains contained functional, potentially transferable, tetracycline resistance genes. This study advances our understanding of the importance of R. intestinalis within the gut ecosystem by elucidating conserved metabolic characteristics among different strains, isolated from different locations. This information will help to devise dietary strategies to increase the abundance of this species providing health benefits.